2015
DOI: 10.1155/2015/873751
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Study of the Lingula in Adult Human Mandibles of Brazilians Individuals and Clinical Implications

Abstract: Objectives. The purpose of this research was to study, in macerated adult human mandibles, the height of the lingula and provide morphometric data for its location considering aspects such as shape of the lingula, gender, and race. Material and Methods. 132 macerated mandibles of Brazilian adult individuals, both sexes, Amerindian and Caucasian, were used. The distances: from mandibular notch to lingula; from anterior margin of ramus of mandible to lingula; from posterior margin of ramus of mandible to lingula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 16 publications
1
26
1
1
Order By: Relevance
“…The mandibular foramen position is used as a parameter for safe interventions involving the mandibular ramus region, including surgery and anaesthesia [ 30 ], and this helps reduce complications due to inferior alveolar vasculonervous bundle lesions [ 31 ]. In a study of macerated mandibles in Brazilian individuals, Alves and Deana [ 32 ] performed morphological analysis of the mandibular lingula superoinferior position, an anatomical structure which forms the medial limit of the mandibular foramen [ 1 ]. They reported that the lingula was located in the superior or middle third of the ramus, 1 mm away from the intersection line of these two-thirds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mandibular foramen position is used as a parameter for safe interventions involving the mandibular ramus region, including surgery and anaesthesia [ 30 ], and this helps reduce complications due to inferior alveolar vasculonervous bundle lesions [ 31 ]. In a study of macerated mandibles in Brazilian individuals, Alves and Deana [ 32 ] performed morphological analysis of the mandibular lingula superoinferior position, an anatomical structure which forms the medial limit of the mandibular foramen [ 1 ]. They reported that the lingula was located in the superior or middle third of the ramus, 1 mm away from the intersection line of these two-thirds.…”
Section: Discussionmentioning
confidence: 99%
“…However, we note that previous studies in macerated mandibles did find an association between age and mandibular foramen location, with a more superior location found in younger males compared to older males and a more posterior location found in younger females compared to older females [ 35 ]. Sex, age, and ethnic group must be considered in surgical interventions or anaesthetic blocking, in order to reduce complication risks in this region [ 32 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A relationship has been found between the shape of the lingula and its location in the ramus of the mandible. 27 In general, triangular lingulae were located slightly more posterior than nodular lingulae, and it is important to consider this tendency when performing surgical procedures involving the ramus of the mandible. 27 In this study, the triangular shape was located higher than other shapes.…”
Section: Discussionmentioning
confidence: 99%
“…The mandibular foramen, which is located on the medial aspect of the middle of the ramus, is the entrance to the mandibular canal. The mandibular lingula limits the foramen medially (Alves and Deana, ), and is the attachment of the sphenomandibular ligament, clinically important for oral and maxillofacial surgeons during saggital split ramus osteotomy as a landmark for avoiding nerve injury, hemorrhage and unfavorable fractures (Jansisyanont et al, ). There is a shallow groove (or sometimes a partial canal, or a small bone bridging) located posterior to the lingula called the mylohyoid groove (Narayana et al, ; Mensink et al, ), in which the mylohyoid nerve, a small branch of the inferior alveolar nerve, penetrates.…”
Section: Discussionmentioning
confidence: 99%